2019
DOI: 10.1017/s1751731118001659
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of milk fatty acid profile in sheep: comparison between gas chromatographic measurements and Fourier-transform IR spectroscopy predictions

Abstract: Fatty acid (FA) composition is a key component of sheep milk nutritional quality. However, breeding for FA composition in dairy sheep is hampered by the logistic and phenotyping costs. This study was aimed at estimating genetic parameters for sheep milk FA and to test the feasibility of their routine measurement by using Fourier-transform IR (FTIR) spectroscopy. Milk FA composition of 989 Sarda ewes farmed in 48 flocks was measured by gas chromatography (FAGC). Moreover, FTIR spectrum was collected for each sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
5
14
0
Order By: Relevance
“…Heritability estimates based on pedigree models were consistent with a previous work carried out on a similar data set (Correddu et al, 2018), whereas genomicbased h 2 were higher and lower than pedigree based on SFA (<C14) and UFA, respectively. A large variation among different FA was observed, regardless of the considered approach or the phenotype used, in agreement with previous studies (Sánchez et al, 2010;Boichard et al, 2014).…”
Section: Genetic Parameters Of Milk Fa Profilesupporting
confidence: 87%
See 4 more Smart Citations
“…Heritability estimates based on pedigree models were consistent with a previous work carried out on a similar data set (Correddu et al, 2018), whereas genomicbased h 2 were higher and lower than pedigree based on SFA (<C14) and UFA, respectively. A large variation among different FA was observed, regardless of the considered approach or the phenotype used, in agreement with previous studies (Sánchez et al, 2010;Boichard et al, 2014).…”
Section: Genetic Parameters Of Milk Fa Profilesupporting
confidence: 87%
“…Good prediction accuracies of milk FA based on FTIR spectrum have been reported for dairy cattle (Arnould and Soyeurt, 2009;De Marchi et al, 2011). Similar results, even though with a certain degree of variability and in a limited number of studies, have been reported for dairy sheep (Ferrand-Calmels et al, 2014;Caredda et al, 2016;Correddu et al, 2018). Fatty acid predicted by FTIR exhibited genetic variation both in dairy cattle (e.g., Soyeurt et al, 2007;Bastin et al, 2013;Narayana et al, 2017) and sheep (Sánchez et al, 2010;Boichard et al, 2014).…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations